Dynamics of Interreligious Relations in Indonesian Film Works: A Semiotic and Narrative Analysis - Muhammadiah, Mas'ud (Kamara Journal, 2025)
Indonesia, as a multireligious country, faces challenges in building harmonious relations between religious communities. Film, as a popular cultural medium, plays a crucial role in representing these dynamics. This study aims to analyze how interreligious relations are represented in Indonesian films through a semiotic and narrative approach. Three films were selected as the objects of study: 3 Hati Dua Dunia Satu Cinta (Three Hearts, Two Worlds, One Love), Bumi Itu Bulat (Earth Is Round), and Ayat-Ayat Cinta 2 (Verses of Love 2). The study employed a qualitative method with Roland Barthes' semiotic analysis technique and Todorov's narrative structure. Data were collected through film observation, literature review, and interpretation of symbols and storylines. The analysis shows that the films display religious symbols such as crosses, headscarves, and places of worship as visual signs that are not neutral but contain ideological and emotional meanings. The story structure generally follows a conflict-reconciliation pattern, reinforcing messages of tolerance and empathy across faiths. The main characters are generally portrayed as moderate figures who bridge interfaith dialogue. In conclusion, Indonesian films not only reflect the pluralistic reality of society but also shape social discourse on tolerance and inclusivity. Films function as a means of cultural education and an agent of social transformation in building harmony between religious communities.